Low-frequency rTMS is better tolerated than high-frequency rTMS in healthy people: Empirical evidence from a single session study. (June 2019) - Kaur, Manreena; Michael, Jessica A.; Fitzgibbon, Bernadette M.; Hoy, Kate E.; Fitzgerald, Paul B.
Abstract: Low-frequency and high-frequency repetitive transcranial magnetic stimulation (rTMS) are similarly efficacious for treatment-resistant depression. Low-frequency is posited to be better tolerated than high-frequency rTMS, however, this is not supported by empirical evidence to date. This study aimed to quantify and compare the tolerability of low-versus high-frequency rTMS. Twenty healthy participants (mean age 38.6 ± 13.9 years) underwent low- and high-frequency rTMS administered on left frontal, fronto-central and central sites at 100% resting motor threshold. For the low-frequency protocol, 60 s of 1 Hz stimulation was applied at each site and for the high-frequency protocol, 3 × 5 s trains of 10 Hz stimulation with a 30 s inter-train interval were applied at each site. Tolerance for each stimulation type was assessed immediately after stimulation through participant ratings of overall intensity of scalp sensations, pain, muscle twitching, discomfort and any other sensation. Low-frequency rTMS was significantly less intense than high-frequency rTMS in overall intensity, pain, muscle twitching (all p < .01) and discomfort (p < .001). Limitations of this study include the healthy participant sample and administration of a single session of rTMS. While further work is needed in clinical samples using typical rTMS treatment protocols, these data provide the first evidence that low-frequency is better tolerated than high-frequency. These findings may inform clinical practice of rTMS treatment for depression (and other illnesses) by supporting the application of low-frequency protocols.